Subgroup differences in public attitudes, preferences and self-reported behaviour related to deceased organ donation before and after the introduction of the ‘soft’ opt-out consent system in England: mixed-methods study - Paul Boadu; Leah McLaughlin; Jane Noyes; Stephen O’Neill; Mustafa Al-Haboubi; Lorraine Williams; Jennifer Bostock; Nicholas Mays (BMC Health Services Research)
Abstract Background In the UK, over 7,000 people are on the waiting list for an organ transplant and there are inequalities in need, access and waiting time for organs, with notable differences between minority ethnic groups. In May 2020, England changed the law and introduced a ‘soft’ opt-out system of consent to organ donation with a view to increase consent rates. We aimed to learn more about the impact of the law change on attitudes and views likely to be relevant to consent to deceased organ donation between different population subgroups. Methods Mixed-methods design involving latent class analysis of data from twelve repeated cross-sectional surveys undertaken from 2015 to 2021 (n = 19,011); analysis of the law change survey dataset collected quarterly from 2018 to 2022 (n = 45,439); and interviews with purposively selected members of the public (n = 30) with a focus on minority perspectives. Results Support for the principle of deceased organ donation remained high and stable in the general population (80%) but was 20% lower among ethnic minorities. From 2018 to 2022, an average of 58% of the general population was aware of the law change; this was lower among minority ethnic groups (31%). We identified four population subgroups (supportive donors (24% of the population); unengaged donors (22%); uncommitted donors (46%); and unsupportive donors (9%)). Interview themes included the challenges of discussing organ donation decisions, balancing autonomy with respecting family relationships, targeted misinformation, frustrations at the lack of consensus between community leaders, limited understanding of what happens during the end-of-life care leading to organ donation, and how this aligns with cultural values and preferences. Conclusion Implementation of the law change has not been associated to date with any change in public attitudes and preferences likely to influence consent overall or in minority ethnic groups in England. Uncommitted donors may benefit from encouragement to express their organ donation decision, and unengaged donors from attempts to address mis/information, confusion, and uncertainty. Interventions to raise the consent rate need to take account of the significant role of the family as well as wider community influences on attitudes, preferences and decision-making, particularly among certain minority (ethnic) groups.